1979
DOI: 10.2176/nmc.19.83
|View full text |Cite
|
Sign up to set email alerts
|

Intimal Change following Subarachnoid Hemorrhage Resulting in Prolonged Arterial Luminal Narrowing

Abstract: The luminal surface of the cerebral arteries was examined by scanning electron micro scopy. Preliminary findings of the cases which succumbed to the aneurysmal rupture are reported with those obtained by light microscopic examinations of old autopsy specimens of the ruptured aneurysm.On SEM, the endothelial cells were lost on the luminal surface of the cerebral arteries and some were covered with fibrin meshwork confining red blood cells and other corpuscles.These findings were interpreted as endothelial injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Reports on the action of these platelets and thrombi suggest that arteries are narrowed by mural thrombi as well as by proliferative organic changes in the arterial wall and such narrowing is often confused with prolonged vasospasm [62, 63]. Also, aggregated platelets may release vasoactive substances that produce smooth muscle constriction that results in arterial narrowing [60].…”
Section: Microthrombosismentioning
confidence: 99%
“…Reports on the action of these platelets and thrombi suggest that arteries are narrowed by mural thrombi as well as by proliferative organic changes in the arterial wall and such narrowing is often confused with prolonged vasospasm [62, 63]. Also, aggregated platelets may release vasoactive substances that produce smooth muscle constriction that results in arterial narrowing [60].…”
Section: Microthrombosismentioning
confidence: 99%
“…However, short-term arterial spasm has been difficult to document in humans after aneurysmal SAH [8], but angiographic vasospasm of the basilar artery was progressively greater and prolonged in dogs by successive injections of cisternal blood [31]. In addition, Someda et al [29] reported that endothelial injury in one-hemorrhage dogs occurred initially on day 2 or 3 and was followed by development of endothelial damage accompanied with vasospasm [16,29]. These results suggest that the onset and the severity of endothelial injuries in SAH rats may differ from those in dogs and humans after SAH, and endothelial injuries in dogs occurs initially on day 2 or 3, and progression of the damage is caused by continuous vasospasm after SAH.…”
Section: Discussionmentioning
confidence: 99%